Wild plants : the treasure of natural healers - Rai, Mahendra; Bhattarai, Shandesh, 1977-; Feitosa, Chistiane Mendes (Boca Raton : CRC Press, 2020)
This book offers a broad summary of the wild plants and their usage, as well as the growing interest in ethnopharmacology research. The book comprises of important issues such as diversity of wild plants with emphasis on medicinal and food plants, threats to wild plants and traditional ethnobotanical knowledge, their uses in skin diseases, snake-bites, in cosmeceuticals, etc. Moreover, the ethnopharmacological relevance of wild plants in Latin America has been discussed. The chapters include a wide range of case studies, giving updated evidence on the importance of their wild plant resources from different countries including Peru, Nepal, Bangladesh, India, Pakistan, Brazil. In addition, some specific species are used to explain their potential properties, as well as the dangers of their use without guidance of trained natural healers. The book discusses traditional usage and properties of wild plants and is entirely different from other related publications and useful for the researchers working in the areas of conservation biology, botany, ethnobiology, ethnopharmacology, policymakers, etc.
GENERAL. Wild Plants as a Treasure of Natural Healers: The Need for Unlocking the Treasure. The Disappearance and Substitution of Native Medicinal Species. SPECIFIC COUNTRIES. Wild Plants of Northern Peru: Traditions, Scientific Knowledge and Innovation. Ethnic Uses of Plant Species among Magar People in Nepal. Some Plants Used as Phytomedicine by Tribal Healers of Chittagong Hill Tracts, Bangladesh. Argentinian Wild Plants as Controllers of Fruits Phytopathogenic Fungi: Trends and Perspectives. Plants from Brazil used against Snake Bites: Oleanolic and Ursolic Acids as Antiophidian against Bothrops jararacussu venom. Latin American Endemic (Wild) Medicinal Plants with High-Value: Ethnobotanical, Pharmacological, and Chemical Importance. Phytochemicals from Wild Medicinal and Aromatic Plants of Argentina. The Zig-Zag Trail of Symbiosis among Chepang, Bat, and Butter Tree: An Analysis on Conservation Threat in Nepal. SPECIFIC PLANTS AND AILMENTS. Role of Wild Plants in Curing and Healing the Skin Diseases. Choerospondias axillaris (Hog plum): Multiple Health Benefits. Artemisia Species: Medicinal Values with Potential Therapeutic Uses. The Potential Use of Mandacaru (Cereus spp.) Bioactive Compounds. Subfamily Bombacoideae: Traditional Uses, Secondary Metabolites, Biological Activities and Mechanistic Interpretation of the Anti-Inflammatory Activity. Ayahuasca: Inherent Dangers in Its Consumption. Exploring the Plant Kingdom for Sources of Skincare Cosmeceuticals: From Indigenous Knowledge to the Nanotechnology Era. Ethnomedicinal and Pharmacological Importance of Glycyrrhiza glabra L.
OCLC-licensed vendor bibliographic record.
Keywords: Medicinal plants; Wild plants, Edible; Ethnopharmacology; MEDICAL / Alternative Medicine; SCIENCE / Life Sciences / Botany; HEALTH & FITNESS / Herbal Medications